Urgensi Pendidikan Kaum Perempuan pada Era Globalisasi: Telaah Pemikiran Siti Walidah - Ziana Maulida Savira; Muh Nur Islam Nurdin; Sutrisno Sutrisno (Lembaga Sosial Rumah Indonesia, 2023)
Social constructs have shifted women's participation in education. Differences in role and status have placed women at a disadvantage in accessing education. This research aims to describe the urgency of women's education in the era of globalization from the perspective of Siti Walidah. This research is a literature study that adopts a descriptive method with a critical approach. Data processing is done with the framework proposed by Miles and Huberman. The results show that Siti Walidah personally applies Al-Ashr theology where in life she must make the best use of time. Siti Walidah's educational ideas refer to the concept of